2000
DOI: 10.2337/diabetes.49.5.797
|View full text |Cite
|
Sign up to set email alerts
|

Rates of skeletal muscle and adipose tissue glycerol release in nonobese and obese subjects.

Abstract: Skeletal muscle and adipose tissue lipolysis rates were quantitatively compared in 12 healthy nonobese and 14 insulin-resistant obese subjects for 3.5 h after an oral glucose load using microdialysis measurements of interstitial glycerol concentrations and determinations of local blood flow with 133 Xe clearance in the gastrocnemius muscle and in abdominal subcutaneous adipose tissue. Together with measurements of arterialized venous plasma glycerol, the absolute rates of glycerol mobilization were estimated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
72
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 42 publications
12
72
0
3
Order By: Relevance
“…Furthermore, heterogeneity in adipose tissue [39] and skeletal muscle [16] lipolysis has been reported. In addition, skeletal muscle and adipose tissue lipolysis can respond differently to insulin [40][41][42][43], also in relation to the insulin level [44,45]. Taken together, these factors hamper a clear interpretation of palmitate release in the arm and leg of healthy individuals and diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heterogeneity in adipose tissue [39] and skeletal muscle [16] lipolysis has been reported. In addition, skeletal muscle and adipose tissue lipolysis can respond differently to insulin [40][41][42][43], also in relation to the insulin level [44,45]. Taken together, these factors hamper a clear interpretation of palmitate release in the arm and leg of healthy individuals and diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lipolysis in skeletal muscle appears to be regulated differently. Several studies have demonstrated that insulin does not suppress muscle lipolysis [6][7][8], which may be due to different phosphodiesterase subtypes in the two tissues [9]. With regard to the catecholamine regulation of skeletal muscle lipolysis, disparate findings have been reported.…”
Section: Introductionmentioning
confidence: 86%
“…[7][8][9] In obesity, the insulin-stimulated increase in skeletal muscle and adipose tissue blood flow 2,4 also appears to be blunted. 2 These findings suggest that the decrease in basal and postprandial adipose and skeletal muscle blood flow 9 is because of insulin resistance. Decreased adipose tissue blood flow affects metabolism by decreasing delivery of glucose, fatty acids and hormones to adipose tissue, and by decreasing release of lipolysis products and peptides from fat tissue into the general circulation.…”
Section: Introductionmentioning
confidence: 99%